Does the 3-aminobenzamide effect on bacterial translocation affect experimental acute necrotizing pancreatitis? - Sezai AYDIN; A. Turan IŞIK; Eşref ÇINAR; Oktay DEMİR and Cemal AKAY and Mustafa ÖZYURT and Salih DEVECİ and M. Refik MAS (Turkish Journal of Gastroenterology, 2019)
-